Pediatric visceral leishmaniasis in Albania: a retrospective analysis of 1,210 consecutive hospitalized patients (1995-2009). - Raida Petrela; Loreta Kuneshka; Eli Foto; Ferit Zavalani; Luigi Gradoni (Public Library of Science (PLoS), 2010)
BACKGROUND: Little information is available about infantile visceral leishmaniasis (VL) in Albania as regards incidence, diagnosis and management of the disease. METHODOLOGY/PRINCIPAL FINDINGS: Demographic data, clinical and laboratory features and therapeutic findings were considered in children admitted to University Hospital of Tirana from 1995 to 2009, and diagnosed as having VL. The diagnosis was based on bone-marrow microscopy/culture in 77.5% of patients, serology in 16.1%, and ex juvantibus in 6.4%. A total of 1,210 children were considered, of whom 74% came from urbanized areas. All patients were in the age range 0-14 years, with a median of 4 years. Hepatosplenomegaly was recorded in 100%, fever in 95.4% and moderate to severe anemia in 88% of cases. Concomitant conditions were frequent: 84% had bronchopneumonia; diarrhea was present in 27%, with acute manifestations in 5%; 3% had salmonellosis. First-line therapy was meglumine antimoniate for all patients, given at the standard Sb(v) dosage of 20 mg/kg/day for 21 to 28 days. Two children died under treatment, one of sepsis, the other of acute renal impairment. There were no cases of primary unresponsiveness to treatment, and only 8 (0.67%) relapsed within 6-12 months after therapy. These patients have been re-treated with liposomal amphotericin B, with successful cure. CONCLUSIONS: Visceral leishmaniasis in pediatric age is relatively frequent in Albania; therefore an improvement is warranted of a disease-specific surveillance system in this country, especially as regards diagnosis. Despite recent reports on decreased responses to antimonial drugs of patients with Mediterranean VL, meglumine antimoniate treatment appears to be still highly effective in Albania.